2017
DOI: 10.14569/ijacsa.2017.080945
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Forecasting Scheme for Financial Time-Series Data using Neural Network and Statistical Methods

Abstract: Abstract-Currently, predicting time series utilizes as interesting research area for temporal mining aspects. Financial Time Series (FTS) delineated as one of the most challenging tasks, due to data characteristics is devoid of linearity, stationary, noisy, high degree of uncertainty and hidden relations. Several singles' models proposed using both statistical and data mining approaches powerless to deal with these issues. The main objective of this study is to propose a hybrid model, using additive and linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…Faruk [15] has mentioned the superiority of the hybrid models over the ARIMA and neural network models for water quality predictions. Khairalla and AL-Jallad [16] have also obtained similar results in the case of financial time series analysis. Results obtained by Rathod et al [17] have revealed that the forecasting accuracy of the hybrid models is better as compared to the single models and among the hybrid models, the ARIMA-NLSVR model has performed superior than the ARIMA-TDNN model.…”
Section: Introductionsupporting
confidence: 58%
“…Faruk [15] has mentioned the superiority of the hybrid models over the ARIMA and neural network models for water quality predictions. Khairalla and AL-Jallad [16] have also obtained similar results in the case of financial time series analysis. Results obtained by Rathod et al [17] have revealed that the forecasting accuracy of the hybrid models is better as compared to the single models and among the hybrid models, the ARIMA-NLSVR model has performed superior than the ARIMA-TDNN model.…”
Section: Introductionsupporting
confidence: 58%
“…Then, three approaches were examined, namely, ARIMA, EXP, and ANN. Conclusions indicated the advantages of a combination model on all other examined models based on 0.82% MAPE error computing for precision (Khairalla & AL-Jallad, 2017). Recently, some scholars have applied an ANN model on the ground of a tool of their study.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Machine Learning methods have also been used to improve forecasting results. Much research on this has been done, either applying methods independently or combining them with statistical methods [13][14][15][16][17][18][19][20][21][22]. This study tries to predict the net income for next year by using several financial ratios obtained from four leading banks in Indonesia based on time series data modeling by using ARX model.…”
Section: Introductionmentioning
confidence: 99%